2019
DOI: 10.1016/j.jclepro.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

The influence of local officials' promotion incentives on carbon emission in Yangtze River Delta, China

Abstract: China's carbon emissions is heavily influenced by economic growth, which can be largely related to the local officials' promotion incentives. The current study was conducted to test the hypothesis that the influence of local officials' individual characteristics on carbon emissions was driven by the promotion incentives. Yangtze River Delta where carbon emissions accounted for around 13.95% of China's total emissions was selected as the research area. The multiple linear regression model was applied to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Kahn, Li and Zhao [12] found that officials' green performance appraisal system, including environmental governance indicators, incentivize local governors to increase their effort to reduce water. Meng et al [16] used the multiple linear regression model to determine the relationship between local officials' characteristics and total carbon emissions and carbon emissions from different sectors. The results showed that the promotion incentives, tenure and age of local officials have a significant impact on total carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kahn, Li and Zhao [12] found that officials' green performance appraisal system, including environmental governance indicators, incentivize local governors to increase their effort to reduce water. Meng et al [16] used the multiple linear regression model to determine the relationship between local officials' characteristics and total carbon emissions and carbon emissions from different sectors. The results showed that the promotion incentives, tenure and age of local officials have a significant impact on total carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ma et al [33] further note that wealth, economic structure, energy structure, population structure, and the development of technology are also major influential factors of China's carbon emission. Meng et al [34] investigate the impact of local officials' promotion incentives on China's CO 2 emission. e results indicated the significant influence of age, tenure, and local officials' promotion sources on total CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study of Jotzo and Pezzey [10], according to the expected GDP growth in different regions, a model of government low-carbon technology subsidies linked to GDP has been established. Part of the literature uses real corporate data and cases to verify the incentives of local officials' characteristics and government low-carbon technology subsidies for regional carbon emission reduction [11,12].…”
Section: Introductionmentioning
confidence: 99%